2019
DOI: 10.3892/mmr.2019.10107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential diagnostic biomarkers for pneumonia caused by adenovirus infection in children by screening serum exosomal microRNAs

Abstract: Human adenovirus (HAdV) infection causes serious pneumonia in children, leading to significant morbidity and mortality rates. However, diagnostic biomarkers for HAdV-associated pneumonia are unavailable. Serum microRNAs (miRNAs/miRs) have been recently reported as diagnostic biomarkers for several diseases. The present study performed microRNA sequencing to identify potential biomarkers among serum exosomal miRNAs, with the aim of identifying candidate biomarkers for the diagnosis of pneumonia in adenovirus-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 42 publications
3
22
0
4
Order By: Relevance
“…30 A latest study proved that exosomal miR-103a-3p decreased in serum of children with adenovirus infected pneumonia. 12 In accordance with this study, we confirmed that exosomal miR-103a-3p was lowly expressed in blood samples of pneumonia patients and LPS-induced lung cells, MiRNAs are non-coding RNAs, and can mediate cell proliferation, apoptosis and other biological functions by targeting multiple transcription factors. [31][32][33] Previous studies have confirmed that ADAM10 was a target of miR-103a-3p, and silencing of ADAM10 abated the inflammation of murine abdominal aorta.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…30 A latest study proved that exosomal miR-103a-3p decreased in serum of children with adenovirus infected pneumonia. 12 In accordance with this study, we confirmed that exosomal miR-103a-3p was lowly expressed in blood samples of pneumonia patients and LPS-induced lung cells, MiRNAs are non-coding RNAs, and can mediate cell proliferation, apoptosis and other biological functions by targeting multiple transcription factors. [31][32][33] Previous studies have confirmed that ADAM10 was a target of miR-103a-3p, and silencing of ADAM10 abated the inflammation of murine abdominal aorta.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, transfection with miR‐483‐3p promotes the innate immune response, and elevates the expression of IL‐6, CCL2 and TNF‐α . A latest study proved that exosomal miR‐103a‐3p decreased in serum of children with adenovirus infected pneumonia . In accordance with this study, we confirmed that exosomal miR‐103a‐3p was lowly expressed in blood samples of pneumonia patients and LPS‐induced lung cells, and overexpression of miR‐103a‐3p weaken the LPS‐induced immune response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After duplicate removal, the title and abstracts were manually sorted and matched according to the inclusion and exclusion criteria. A total of 16 articles were fully reviewed [7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Afterward, details were extracted for each article as described in methods.…”
Section: Resultsmentioning
confidence: 99%